Short Paper - The Binary Linearization Complexity of Pseudo-Boolean Functions - Walter, Matthias (Open Journal of Mathematical Optimization, 2024)
We consider the problem of linearizing a pseudo-Boolean function f : { 0 , 1 } n → ℝ by means of k Boolean functions. Such a linearization yields an integer linear programming formulation with only k auxiliary variables. This motivates the definition of the linearization complexity of f as the minimum such k . Our theoretical contributions are the proof that random polynomials almost surely have a high linearization complexity and characterizations of its value in case we do or do not restrict the set of admissible Boolean functions. The practical relevance is shown by devising and evaluating integer linear programming models of two such linearizations for the low auto-correlation binary sequences problem. Still, many problems around this new concept remain open.